The effect of using greenhouse for rearing broilers in Iraq. - الجنابي يحيى عباس مرداس; الجنابي ثامر كريم خضير; الطائي سلام مرزة سهيل; الياسري أحمد نوري; مهدي ايمن جاسم (Journal of Kerbala for Agricultural Sciences, 2016)
This study was conducted at the private poultry farm in Jbala at north of Babylon during the period from 1/11/2015 to 12/12/2015. The aim of this study was to investigate the effect of using greenhouse for rearing broilers. Two kinds of poultry halls were used in this study, the first one was greenhouse hall presented T1 treatment and the second was traditicnal poultry hall represented T2 treatment. A total of 900 Ross 308 broilers chicks were used in each treatment. At each hall were selected three locations at the beginning, middle, and the end of hall. These locations presented the replicates of each treatment. The area of each location was 30m2. The chicks were randomly distributed into the replicates. Each replicate had 300 chicks and each hall had 1800 chicks. The fed was free at all period of the study and the light program was 24 hours. The results refer to no significant effects between greenhouse hall and regular hall on body weight, feed intake, weight gain, feed conversion ratio and percentages of mortality.